2011
DOI: 10.1007/s10120-011-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the accuracy and indications for diagnostic laparoscopy prior to curative-intent resection of gastric cancer

Abstract: Despite evolving preoperative imaging techniques, diagnostic laparoscopy continues to be of substantial value in staging patients with gastric cancer and in avoiding unnecessary laparotomy. The current data support DL for all patients with advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 43 publications
3
81
0
7
Order By: Relevance
“…These high re-staging rates support the use of diagnostic laparoscopy (DL) to clarify pre-operative intent. Our review on the use of DL in gastric cancer found that DL changed management in 10-60% of cases [69].…”
Section: Overallmentioning
confidence: 94%
“…These high re-staging rates support the use of diagnostic laparoscopy (DL) to clarify pre-operative intent. Our review on the use of DL in gastric cancer found that DL changed management in 10-60% of cases [69].…”
Section: Overallmentioning
confidence: 94%
“…Given that the accuracy of ct imaging in detecting M1 disease is 81% 66 , diagnostic laparoscopy could allow patients to avoid a laparotomy in up to 44% of cases of advanced-stage cancer 67 . Guidelines from both the Scottish Intercollegiate Guidelines Network 68 Surgeons 69 suggest diagnostic laparoscopy in patients with clinically suspected T3 and T4 cancers or in those at higher risk for M1 disease, such as those with poorly differentiated cancers and with a higher nodal burden.…”
Section: Qualifying Statements For Recommendationmentioning
confidence: 99%
“…It can therefore prevent an unnecessary explorative laparotomy or change management in up to 60% of cases [50,51] . An expert panel concluded that a staging laparoscopy should be performed for reasons mentioned above, exceptions being early gastric cancer or known metastatic disease [52] .…”
Section: Staging Laparoscopy and Wash Cytologymentioning
confidence: 99%